2013
DOI: 10.5935/0101-2800.20130020
|View full text |Cite
|
Sign up to set email alerts
|

Is there association between acyl-ghrelin and inflammation in hemodialysis patients?

Abstract: Hemodialysis patients showed low acyl-ghrelin levels and seem to present an acyl-ghrelin resistance and there was no correlation between inflammation and this orexigenic hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
2
9
1
1
Order By: Relevance
“…Due to these changes; anorexia, increased energy consumption, depletion of the protein stores, destruction in adipose and muscle tissues occur. 10 Leptin and ghrelin are neurohormones involved in appetite and energy metabolism and released from gastric mucosa. Ghrelin stimulates food intake, reduce energy consumption and lead to weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these changes; anorexia, increased energy consumption, depletion of the protein stores, destruction in adipose and muscle tissues occur. 10 Leptin and ghrelin are neurohormones involved in appetite and energy metabolism and released from gastric mucosa. Ghrelin stimulates food intake, reduce energy consumption and lead to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin and leptin are hormones that have critical role in regulation of appetite and also related with inflammation. [10][11][12] Hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) are techniques commonly used in maintenance of patients with CRF until renal transplantation. Although there are many reports about these two methods in patients with end-stage renal disease (ESRD), it is still uncertain which one contributes to prolonged survival.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of appetite reduces the intake of dietary energy and other nutrients and leads to weight loss and malnutrition progression ( 4 ). Nevertheless, uremic toxins stimulate disorders of the central nervous system and adipose tissue ( 2 ), which may affect diminished appetite ( 2 , 5 , 6 ). Leptin, “a negative acute phase protein,” is secreted by adipose tissue and acts on the hypothalamus in order to regulate food intake and energy expenditure ( 2 , 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Barros et al reported that the serum ghrelin levels were significantly higher in hemodialysis patients, but no significant correlation was found between the inflammatory and ghrelin factors (24). In addition, in a study on menopause women, no significant association between the ghrelin levels and ALP was observed (18,25).…”
Section: Discussionmentioning
confidence: 99%